Complete real-time temporal waveform characterization of single-shot few-cycle laser pulses - Chen, Zhangjin; Wittmann, T.; Horvath, B.; Lin, C. D. (My University, 2009)
A method for complete characterization of the waveform of individual few-cycle laser pulses is presented. By analyzing the “left” and “right” asymmetries of high-energy photoelectrons along the polarization axis using the recently developed quantitative rescattering theory, we show that the carrier-envelope phase (CEP), pulse duration, and peak intensity of each single-shot pulse can be readily retrieved. By CEP tagging each laser shot, the method permits the study of waveform-dependent processes be extended to relativistic beams and to wavelengths, where CEP stabilization is not yet possible.